Endocytosis‐Enabled Construction of Silica Nanochannels Crossing Living Cell Membrane for Transmembrane Drug Transport. (19th July 2020) - Pan, Xi; Xu, Dandan; Tang, Xiuzhen; Liu, Ning; You, Yongqiang; Wang, Xianqiao; Yan, Xiaohui; Ma, Xing; Chen, Xiaoyuan
Abstract: Artificial transmembrane channel (ATC) analogs are developed for overcoming biological membrane barriers and realizing transmembrane drug delivery, which are mostly studied within artificial lipid bilayers and thus lacked enough stability in practical applications on living cells. Here, natural endocytosis of silica‐based 1D nanomaterials (nanowires) with an ultrahigh aspect ratio is investigated. Enlightened by partially endocytosed ultralong silica nanowires, ATC that can penetrate living cell membranes for transmembrane transportation of small drug molecules is creatively constructed, resulting in enhanced drug delivery efficacy and decreased the half maximal inhibitory concentration. For the first time, an in‐depth study of the cellular uptake of 1D nanomaterials with ultrahigh aspect ratios (from 10 to 120) into living cells is carried out. Through confocal laser scanning microscopy observation, the endocytosis process of ultralong nanowires, including full uptake of short nanowires and partial uptake of longer nanowires, is clarified. Theoretical simulation is performed to give a fundamental understanding on the endocytosis mechanism of ultralong 1D silica nanowires. The simulation results demonstrate the time‐dependent internalization dynamics of the nanowires, which agrees well with our experimental results. This work not only clarifies the cellular interaction between 1D nanomaterials and living cells, but also pioneers the use of natural endocytosis of 1D nanomaterials for constructing ATC. Abstract : Here, the natural endocytosis process and mechanism of silica‐based 1D nanomaterials (nanowires) with ultrahigh aspect ratio are investigated, which demonstrate two endocytosis scenarios (full and partial) and the time‐dependent internalization behavior of the nanowires. The use of partially endocytosed ultralong nanowires is pioneered for constructing artificial transmembrane channels for transmembrane drug transport.